Are there limits to growth of tourism on the Caribbean islands? Case-study Aruba - Jurgens, Sharona S.; Mijts, Eric; Van Rompaey, Anton (Frontiers in Sustainable Tourism, 2024)
Mass tourism is a major driver of economic growth in the Caribbean. One major trade-off of this economic growth model is the loss of natural areas due to tourism activities and increasing urbanization. Aruba is one of the most tourist intense destinations within the region with a total of 1.1 million stay-over tourists in 2019. Moreover, this island has one of the largest population densities in the Caribbean and high-speed urbanization takes place in this formerly rural island state. Therefore, this study aims to assess the islands' carrying capacity in relation to its limited land resources by means of a geospatial methodological analysis coupled with a correlation analysis between socio-economic indicators and statistics. First, the past and present drivers and characteristics of urbanization are analyzed. Second, the correlation between socio-economic indicators and the number of tourists was assessed. Third, two future scenarios were developed to assess the maximum carrying capacity. From 1986 till 2020, Aruba's built environment increased from 29–60 km2 and translates to one-third of the island. Expansion was characterized by sprawl in the earlier years and changed to infilling in the latter. Furthermore, the results indicate that all socio-economic indicators are strongly positive correlated to tourism. Lastly, the possible maximum physical carrying capacity for yearly visitors and number of inhabitants was calculated to be 1.7 million and 150.000, respectively. We conclude that the proposed methodological framework is robust and adequate to serve as a low budget decision-making tool for sustainable tourism development on islands.